Development and Validation of an Overall Equipment Efficiency Measurement Model for Supporting Operational Excellence. Issue 10 (2022) - Kiridena, Senevi; Li, Wenxu; Dwight, Richard
Abstract: This paper reports on an empirical study undertaken to investigate the overall equipment effectiveness (OEE) of several strategically selected production lines in a manufacturing plant. The study involved the development and application of bespoke data acquisition systems to capture shop-floor level data, as well as the validation of a novel OEE model that accounts for a set of industry-specific requirements and conditions. Based on the analysis of data acquired from a number of production lines within the plant over several months of operation, an OEE model that computes the ratio of the target time, with no disruptions during production, to the actual time, was proposed. Novel methods for discriminating delays and delay causes from production time were also validated. The significant time losses identified were related to changeover, order change, and raw material loading. The measure proposed can be applied at the level: including organisation, production line, product, or order. A number of measures for improving OEE are proposed.